Implementation of Islamic Educational Leadership in the Digital Era Among Gen Z - Mashuri, Mashuri; Junaidi, Junaidi; Ramadona, Aulia; Amelia, Lia; Yusri, Yusnimar (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background. The digital era has brought about significant changes in communication, learning, and leadership patterns, including in the context of Islamic education. Generation Z, born and raised alongside the development of digital technology, possesses unique characteristics such as technological literacy, critical thinking, and individualistic tendencies. Purpose. This study aims to examine how to implement effective Islamic educational leadership in the digital era, especially in fostering and guiding students from Generation Z. The main focus is to identify appropriate leadership models, strategies used, and challenges faced in managing contextual and digital-friendly Islamic education. Method. This research employed a qualitative approach with a literature review. Data were collected from various scientific journals, books, and relevant research reports on Islamic educational leadership, the characteristics of Gen Z, and the influence of digitalization in education. The analysis was conducted descriptively and critically to identify significant thematic patterns and synthesize them. Results. The study results show that transformational and participatory leadership that utilizes digital platforms such as social media, e-learning, and online communication is very effective in reaching Gen Z. Educational leaders who are able to act as spiritual and digital role models have a significant influence on the formation of Islamic character in this generation. Conclusion. Implementing Islamic educational leadership in the digital era requires leaders who are adaptive, visionary, and capable of integrating Islamic values with digital technology. For Gen Z, a collaborative, communicative, and digitally savvy approach is more effective in creating a religious, dynamic, and relevant learning environment.